Perceptions of a group of nurses on the process of caring for patients with permanent colostomy - Santana, Julio Cesar Batista; Souza, Ângela Batista de; Dutra, Bianca Santana (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to understand the perceptions of a group of nurses on the process of taking care for patients with permanent colostomy. Methodology: it’s a qualitative research focused on phenomenology. It was carried out by eight nurses from the Specialized Course in Family Health, Institute of Continuing Education PUC Minas. This project was approved by the Ethics Committee of the Pontifical Catholic University of Minas Gerais, paragraph number CAAE: 0101.0.213.000-10. The data collection was done through recorded interviews, directed into the following question: What’s the meaning of taking care of patients with irreversible ostomies? Results: the following categories were raised: The importance of nurses orientation to face the illness, the challenges of the nurses to deal with the acceptance of the patients to their new situation, implementation of nursing care: fundamental aspect of quality of life of stoma. Conclusion: it emphasizes the need of creating systematic nursing actions that contribute to a better quality of life and a greater acceptance of the changes caused by the ostomy in every stages of life in people with a stoma. It’s needed a holistic and humane look to take care of a stoma’s patient. Descriptors: ostomy; perception; nursing care; family health; specialization. RESUMO Objetivo: compreender as percepções de um grupo de enfermeiras sobre o processo do cuidar de pacientes portadores de ostomia definitiva. Metodologia: trata-se de pesquisa qualitativa com enfoque na fenomenologia. Foi realizada com oito enfermeiras do Curso de Especialização em Saúde da Família, pelo Instituto de Educação Continuada PUC Minas. Esse projeto foi aprovado pelo Comitê de Ética da Pontifícia Universidade Católica de Minas Gerais pelo n° CAAE: 0101.0.213.000-10. A coleta dos dados foi por meio de entrevistas gravadas, contemplando a seguinte questão norteadora: Qual o significado de cuidar de pacientes portadores de ostomias definitivas? Resultados: emergiram as seguintes categorias: Importância da orientação dos enfermeiros para o enfrentamento da doença, Desafios dos enfermeiros em trabalhar com a aceitação do paciente á nova situação, Implementação dos cuidados de Enfermagem: aspecto fundamental de qualidade de vida do ostomizado. Conclusão: ressalta-se a necessidade de criar ações sistematizadas de enfermagem que contribuem para uma melhor qualidade de vida, e maior aceitação das alterações causadas pela ostomia em todas as fazes da vida da pessoa ostomizada. É preciso um olhar holístico e humanizado ao cuidar do paciente ostomizado. Descritores: ostomia; percepção; cuidados de enfermagem; saúde da família; especialização. RESUMEN Objetivo: Conocer las percepciones de un grupo de enfermeras en el proceso de atención a pacientes con colostomía permanente. Metodología: la investigación cualitativa con un enfoque en la fenomenología. Se llevó a cabo con ocho enfermeras Especialização Curso de Salud de la Familia, Instituto de Educación Continua de la PUC Minas. Este proyecto fue aprobado por el Comité de Ética de la Pontificia Universidad Católica de Minas Gerais por CAAE párrafo: 0101.0.213.000-10. La recolección de datos fue a través de entrevistas, contemplando la siguiente pregunta: ¿Cuál es el significado del cuidado para los pacientes con ostomías final? Resultados: surgieron las siguientes categorías: Importancia de la orientación de las enfermeras para hacer frente a la enfermedad, los desafíos de las enfermeras a trabajar con el paciente acepta la nueva situación, la aplicación de cuidados de enfermería: un aspecto fundamental de la calidad de vida de estoma. Conclusión: se hace hincapié en la necesidad de que las acciones de enfermería sistemática que contribuyen a una mejor calidad de vida, y una mayor aceptación de los cambios causados ​​por la ostomía en todas las etapas de la vida de las personas con un estoma. Se echa un vistazo a la atención integral y humana a estoma del paciente. Descriptores: estomia; percepción; atención de enfermería; salude de la familia; especialización. <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; > <! [endif] > Objetivo: compreender as percepções de um grupo de enfermeiras sobre o processo do cuidar de pacientes portadores de ostomia definitiva. Metodologia: pesquisa qualitativa com enfoque na fenomenologia. Foi realizada com 08 enfermeiras do curso de especialização em Saúde da Família, pelo Instituto de Educação Continuada PUC Minas. A coleta dos dados foi por meio de entrevistas gravadas, contemplando a seguinte questão norteadora: Qual o significado de cuidar de pacientes portadores de ostomias definitivas? Resultados: emergiram as seguintes categorias: Importância da orientação dos enfermeiros para o enfrentamento da doença, Desafios dos enfermeiros em trabalhar com a aceitação do paciente á nova situação, Implementação dos cuidados de Enfermagem: aspecto fundamental de qualidade de vida do ostomizado. Conclusão: ressalta-se a necessidade de criar ações sistematizadas de enfermagem que contribuem para uma melhor qualidade de vida, e maior aceitação das alterações causadas pela ostomia em todas as fazes da vida da pessoa ostomizada. É preciso um olhar holístico e humanizado ao cuidar do paciente ostomizado. Descritores: ostomia; percepção; cuidados de enfermagem; saúde da família; especialização.< > ABSTRACT <span style="font-family: "Trebuchet MS","sans-serif"; background: white; font-size: 9pt; mso-ansi-language: EN-US;" mce_style="font-family: "Trebuchet MS","sans-serif"; background: white; font-size: 9pt; mso-ansi-language: EN-US;" lang="EN-US">Objective: to understand the perceptions of a group of nurses on the process of caring for patients with permanent colostomy. Methodology: qualitative research with a focus on phenomenology. It was conducted with eight nurses Epecialização Course in Family Health, Institute of Continuing Education PUC Minas. This project was approved by the Ethics Committee of the Pontifical Catholic University of Minas Gerais by paragraph CAAE: 0101.0.213.000-10. Data collection was through interviews, contemplating the following question: What is the meaning of caring for patients with ostomies final? Results: emerged the following categories: Importance of the orientation of nurses to cope with the disease, Challenges of nurses to work with the patient will accept the new situation, implementation of nursing care: fundamental aspect of quality of life of stoma. Conclusion: it emphasizes the need for systematic nursing actions that contribute to a better quality of life, and greater acceptance of the changes caused by the ostomy at all stages of life of people with a stoma. It takes a look at holistic and humane care to the patient's stoma. Descriptors: ostomy; perception; nursing care; <span style="font-family: "Trebuchet MS","sans-serif"; color: black; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; color: black; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" lang="ES">family health; specialization. RESUMO Objetivo: compreender as percepções de um grupo de enfermeiras sobre o processo do cuidar de pacientes portadores de ostomia definitiva. Metodologia: trata-se de pesquisa qualitativa com enfoque na fenomenologia. Foi realizada com oito enfermeiras do Curso de Epecialização em Saúde da Família, pelo Instituto de Educação Continuada PUC Minas. Esse projeto foi aprovado pelo Comitê de Ética da Pontifícia Universidade Católica de Minas Gerais pelo n° CAAE: 0101.0.213.000-10. A coleta dos dados foi por meio de entrevistas gravadas, contemplando a seguinte questão norteadora: Qual o significado de cuidar de pacientes portadores de ostomias definitivas? Resultados: emergiram as seguintes categorias: Importância da orientação dos enfermeiros para o enfrentamento da doença, Desafios dos enfermeiros em trabalhar com a aceitação do paciente á nova situação, Implementação dos cuidados de Enfermagem: aspecto fundamental de qualidade de vida do ostomizado. Conclusão: ressalta-se a necessidade de criar ações sistematizadas de enfermagem que contribuem para uma melhor qualidade de vida, e maior aceitação das alterações causadas pela ostomia em todas as fazes da vida da pessoa ostomizada. É preciso um olhar holístico e humanizado ao cuidar do paciente ostomizado. Descritores: ostomia; percepção; cuidados de enfermagem; saúde da família; especialização. <span style="font-family: "Trebuchet MS","sans-serif"; font-size: 10pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 10pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">RESUMEN <span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">Objetivo: conocer las percepciones de un grupo de enfermeras en el proceso de atención a pacientes con colostomía permanente. Metodología: la investigación cualitativa con un enfoque en la fenomenología. Se llevó a cabo con ocho enfermeras Epecialização Curso de Salud de la Familia, Instituto de Educación Continua de la PUC Minas. Este proyecto fue aprobado por el Comité de Ética de la Pontificia Universidad Católica de Minas Gerais por CAAE párrafo: 0101.0.213.000-10. La recolección de datos fue a través de entrevistas, contemplando la siguiente pregunta: ¿Cuál es el significado del cuidado para los pacientes con ostomías final? Resultados: surgieron las siguientes categorías: Importancia de la orientación de las enfermeras para hacer frente a la enfermedad, los desafíos de las enfermeras a trabajar con el paciente acepta la nueva situación, la aplicación de cuidados de enfermería: un aspecto fundamental de la calidad de vida de estoma. Conclusión: se hace hincapié en la necesidad de que las acciones de enfermería sistemática que contribuyen a una mejor calidad de vida, y una mayor aceptación de los cambios causados <span style="font-family: "Arial Unicode MS","sans-serif"; font-size: 9pt; mso-fareast-language: JA; mso-ascii-font-family: 'Trebuchet MS'; mso-ansi-language: ES;" mce_style="font-family: "Arial Unicode MS","sans-serif"; font-size: 9pt; mso-fareast-language: JA; mso-ascii-font-family: 'Trebuchet MS'; mso-ansi-language: ES;" lang="ES">​​<span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">por la ostomía en todas las etapas de la vida de las personas con un estoma. Se echa un vistazo a la atención integral y humana a estoma del paciente. Descritores: <span style="font-family: "Trebuchet MS","sans-serif"; color: black; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; color: black; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" lang="ES">estomia<span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">; percepción; atención de enfermería; salude de la familia; especialización.< > ABSTRACT <span style="font-family: "Trebuchet MS","sans-serif"; background: white; font-size: 9pt; mso-ansi-language: EN-US;" mce_style="font-family: "Trebuchet MS","sans-serif"; background: white; font-size: 9pt; mso-ansi-language: EN-US;" lang="EN-US">Objective<span style="font-family: "Trebuchet MS","sans-serif"; background: white; font-size: 9pt; mso-ansi-language: EN-US;" mce_style="font-family: "Trebuchet MS","sans-serif"; background: white; font-size: 9pt; mso-ansi-language: EN-US;" lang="EN-US">: to understand the perceptions of a group of nurses on the process of taking care for patients with permanent colostomy. Methodology: it’s a qualitative research focused on phenomenology. It was carried out by eight nurses from the Specialized Course in Family Health, Institute of Continuing Education PUC Minas. This project was approved by the Ethics Committee of the Pontifical Catholic University of Minas Gerais, paragraph number CAAE: 0101.0.213.000-10. The data collection was done through recorded interviews, directed into the following question: What’s the meaning of taking care of patients with irreversible ostomies? Results: the following categories were raised: The importance of nurses orientation to face the illness, the challenges of the nurses to deal with the acceptance of the patients to their new situation, implementation of nursing care: fundamental aspect of quality of life of stoma. Conclusion: it emphasizes the need of creating systematic nursing actions that contribute to a better quality of life and a greater acceptance of the changes caused by the ostomy in every stages of life in people with a stoma. It’s needed a holistic and humane look to take care of a stoma’s patient. Descriptors: ostomy; perception; nursing care; <span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" lang="ES">family health; specialization. RESUMO Objetivo: compreender as percepções de um grupo de enfermeiras sobre o processo do cuidar de pacientes portadores de ostomia definitiva. Metodologia: trata-se de pesquisa qualitativa com enfoque na fenomenologia. Foi realizada com oito enfermeiras do Curso de Especialização em Saúde da Família, pelo Instituto de Educação Continuada PUC Minas. Esse projeto foi aprovado pelo Comitê de Ética da Pontifícia Universidade Católica de Minas Gerais pelo n° CAAE: 0101.0.213.000-10. A coleta dos dados foi por meio de entrevistas gravadas, contemplando a seguinte questão norteadora: Qual o significado de cuidar de pacientes portadores de ostomias definitivas? Resultados: emergiram as seguintes categorias: Importância da orientação dos enfermeiros para o enfrentamento da doença, Desafios dos enfermeiros em trabalhar com a aceitação do paciente á nova situação, Implementação dos cuidados de Enfermagem: aspecto fundamental de qualidade de vida do ostomizado. Conclusão: ressalta-se a necessidade de criar ações sistematizadas de enfermagem que contribuem para uma melhor qualidade de vida, e maior aceitação das alterações causadas pela ostomia em todas as fazes da vida da pessoa ostomizada. É preciso um olhar holístico e humanizado ao cuidar do paciente ostomizado. Descritores: ostomia; percepção; cuidados de enfermagem; saúde da família; especialização. <span style="font-family: "Trebuchet MS","sans-serif"; font-size: 10pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 10pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">RESUMEN<span style="font-family: "Trebuchet MS","sans-serif"; font-size: 10pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 10pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES"> <span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">Objetivo<span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">: Conocer las percepciones de un grupo de enfermeras en el proceso de atención a pacientes con colostomía permanente. Metodología: la investigación cualitativa con un enfoque en la fenomenología. Se llevó a cabo con ocho enfermeras Especialização Curso de Salud de la Familia, Instituto de Educación Continua de la PUC Minas. Este proyecto fue aprobado por el Comité de Ética de la Pontificia Universidad Católica de Minas Gerais por CAAE párrafo: 0101.0.213.000-10. La recolección de datos fue a través de entrevistas, contemplando la siguiente pregunta: ¿Cuál es el significado del cuidado para los pacientes con ostomías final? Resultados: surgieron las siguientes categorías: Importancia de la orientación de las enfermeras para hacer frente a la enfermedad, los desafíos de las enfermeras a trabajar con el paciente acepta la nueva situación, la aplicación de cuidados de enfermería: un aspecto fundamental de la calidad de vida de estoma. Conclusión: se hace hincapié en la necesidad de que las acciones de enfermería sistemática que contribuyen a una mejor calidad de vida, y una mayor aceptación de los cambios causados <span style="font-family: "Arial Unicode MS","sans-serif"; font-size: 9pt; mso-fareast-language: JA; mso-ascii-font-family: 'Trebuchet MS'; mso-ansi-language: ES;" mce_style="font-family: "Arial Unicode MS","sans-serif"; font-size: 9pt; mso-fareast-language: JA; mso-ascii-font-family: 'Trebuchet MS'; mso-ansi-language: ES;" lang="ES">​​<span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">por la ostomía en todas las etapas de la vida de las personas con un estoma. Se echa un vistazo a la atención integral y humana a estoma del paciente. Descriptores: <span style="font-family: "Trebuchet MS","sans-serif"; color: black; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; color: black; font-size: 9pt; mso-bidi-font-weight: bold; mso-ansi-language: ES;" lang="ES">estomia<span style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" mce_style="font-family: "Trebuchet MS","sans-serif"; font-size: 9pt; mso-fareast-font-family: 'MS Mincho'; mso-fareast-language: JA; mso-ansi-language: ES;" lang="ES">; percepción; atención de enfermería; salude de la familia; especialización.<–>